The Relationship between female Breast Cancer and Renal Failure (Article Type: Review): Hubungan antara Kanker Payudara Wanita dan Gagal Ginjal (Jenis Artikel: Ulasan) - Jaber, Muntadher Mohammed; Abbas, Adyan Nafea; Anah, Ahmed Hassan Salih Al-Bo; Hanoon, Samer Kareem; Alrabea, Falah Herez Madhloom (Indonesian Journal on Health Science and Medicine, 2024)
Following up on existing statistics and evaluating published research, we discovered that a quarter of women worldwide suffer from cancer, specifically breast cancer, which has a high fatality rate.Renal insufficiency and breast cancer etiology seem to be related in a reciprocal way. When choosing a course of treatment, this association should be taken into account. This study investigates the correlation between these two traits in patients diagnosed with breast cancer. This research paper will look into the relationship between this malignancy and kidney failure in order to determine the best treatment method. As a result, all medical and laboratory methodologies and standards must be used to determine the relationship and direct link between the two disorders. This does not indicate that there is no kidney failure owing to the lack of cancer, but due to cancer, an increase in blood calcium can occur, or due to tumor lysis syndrome (TLS), which causes renal failure in a patient who has kidney functions performing without any pathological defects. The patient's basal glomerular filtration rate should be considered by medical professionals when deciding on the optimal course of treatment for each breast cancer patient. Neglect and lack of regular monitoring of body functions, especially kidney function, through tests and monitoring of the glomerular filtration rate can increase the risk of kidney failure. When comparing cancer patients, meaning breast cancer, who suffer from kidney failure with those whose glomerular filtration rate is within the normal range, we find that the first group has high mortality rates. Therefore, these mortality rates must be reduced through scientific study and investigation to reach somewhat acceptable results. Both breast cancer and renal failure seem to share a common pathogenesis. This association should be taken into consideration while selecting a treatment approach. Physicians should consider the baseline glomerular filtration rate (GFR) of patients with breast cancer when deciding on the optimal course of therapy. Highlights: Investigate breast cancer and kidney failure correlation impacting treatment approaches. High blood calcium or TLS may induce renal failure in patients. Monitor glomerular filtration rate to reduce mortality in affected patients. Keywords: breast cancer, renal failure, tumor lysis syndrome (TLS), glomerular filtration rate (GFR).